1989
DOI: 10.1159/000138613
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Drug-Metabolizing Enzymes in the Cortex and Medulla of the Human Kidney

Abstract: The cortex and medulla were isolated from kidneys whose donors (5 men and 1 woman, aged between 44 and 68 years) were undergoing nephrectomy to remove a tumor. Kidneys with normal architecture for at least two thirds of the organ were included in the study. Tissue specimens used in our experiments were free from pathological changes. The activities of the following enzymes of phase INADPH cytochrome c reductase, aminopyrine N-demethylase, ethoxycoumarin O-deethylase, ethoxyresorufin O-deethylase, microsomal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 10 publications
2
4
0
1
Order By: Relevance
“…The present results on hepatic and renal TPMT activities agree with those in the liter ature [3,18]. A comparison of human fetal and adult lungs and intestinal mucosae is difficult because of the lack of data.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The present results on hepatic and renal TPMT activities agree with those in the liter ature [3,18]. A comparison of human fetal and adult lungs and intestinal mucosae is difficult because of the lack of data.…”
Section: Resultssupporting
confidence: 87%
“…The isoenzyme composition in hu man liver is still unknown. Our previous work on the distribution of the drug-metabolizing enzymes between cor tex and medulla has demonstrated that both TPMT and thiol methyltransferase have higher activity in the renal cortex than me dulla [19]. The present results show that the average of the renal TPMT is about double that of hepatic activity.…”
Section: Resultssupporting
confidence: 58%
“…Tischler and Allen (1985) reported differences in and Km for a number of substrates in tests with crude preparations of TTase from a variety of rat tissues, suggesting tissue-specific variation in TTase. None of these previous studies reported activity in RBCs; however, we have detected TTase activity in bovine RBCs.5 Although evidence for TTase activity in human kidney was reported recently (Pacifici et al, 1989), to out knowledge placental TTase is the only other human TTase that has been purified and studied (Larson et al, 1985;Wells et al, 1990). The limited information reported about the characteristics of the placental enzyme, however, gave its molecular weight as 6000 (Larson, et al, 1985) rather than 11 000-12000 like HRBC TTase and analogous TTases and glutaredoxins from other species; however, the human placental enzyme displayed catalytic activities similar to those of other mammalian TTases (Larson et al, 1985;Wells et al, 1990), and it was reported to cross-react with antibodies against calf 3 H. El Messeery and J. J. Mieyal, unpublished observations.…”
Section: Discussionmentioning
confidence: 58%
“…Im Gegensatz dazu werden MRP2-Transporter vermehrt auf apikalen Membranen gefunden, wodurch Metabolite eher über die Gallenflüssigkeit in den Verdauungstrakt gelangen. [43] All diese Prozesse finden in unterschiedlich starker Ausprägung in verschiedenen Teilen des menschlichen Körpers statt, unter anderem auch in der Niere, der Milz und dem respiratorischen Trakt, [18,[44][45][46][47][48][49][50][51][52][53][54] wobei die Leber wohl den wichtigsten und bekanntesten Vertreter der Stoffwechselorgane darstellt. [38,39,[55][56][57] Die Leber ist unter anderem zuständig für die Verwertung spezifischer Bestandteile aus Lebensmitteln und den Abbau von Metaboliten, Medikamenten und Toxinen.…”
Section: Hauptschritte Des Fremdstoffmetabolismus Und Seine Funktionunclassified